PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN KEAKTIFAN GURU DALAM MENGIKUTI MGMP TERHADAP KINERJA GURU - Saroh, Ida; Latifah, Lyna (Dinamika Pendidikan, 2014)
Nowadays, the teachers’ performance did not meet the expectation based on the competencies. There were many problems related to their performance such as; only a few teachers who did classroom action research, creating the lesson plans which were not supported by the learning media, the lack of learning sources, delivering the lesson without using creative learning so students were difficult to get the lesson. The factors which could influence the teachers’ performance were the principals’ leadership, the teachers’ activeness to join the Subject Teachers Forum/ Musyawarah Guru Mata Pelajaran (MGMP). Thus; the problem of the study: was there any influence of the principals’ leadership, the teachers’ activeness to join MGMP toward the Economics/ Accounting teachers’ performance of Senior High Schools in Kendal either partially or simultaneously? It was a population research so 35 Economics/ Accounting teachers of State Senior High Schools in Kendal as the samples. The data were analyzed by percentage descriptive analysis and doubled linear regression analysis. Based on the result of the study; simultaneously the principals’ leadership and the teachers’ activeness to join MGMP influenced positively and significantly up to 55.5% toward the Economics/ Accounting teachers’ performance of State Senior High Schools in Kendal and partially, the 1st variable (The principals’ leadership) influenced up to 43.16%, whereas the 2nd variable (The teachers’ activeness) influenced only 16%.